Revisão teórica: cultivo de microalgas para a produção de carotenoides - Soares, Laura Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
The microalgae industry has received significant attention with the search for more natural products and as the concern for the environment has become increasingly frequent. These microorganisms are capable of producing several metabolites with high added value, including carotenoids. Due to health benefits and their pigments, the demand for natural carotenoids has increased in recent years. They can be used in food, animal feed, cosmetics, and nutraceutical industries, however there are challenges associated with their microalgae mass production, the main one being the uncompetitive cost compared to alternative products obtained by chemical synthesis. This review aimed to study the carotenoids produced by microalgae; the main influencing factors; and the analysis of the industrial viability of this pigment, mainly in Brazil. According to estimates, the global carotenoid market is expected to reach USD 2.0 billion in 2026, and Brazil, in 2019, imported USD 3.5 million of carotenoids. The dyes nationally produced are mostly through vegetal extraction, which makes the production by biotechnological way a potential to be explored in the country. The use of microalgae as raw material for carotenoids is expected to grow as much research has been carried out with the aim of optimizing this production and making it more and more marketable.

A indústria de microalgas tem recebido atenção significativa com a busca por produtos mais naturais e a preocupação com o meio ambiente tem se tornando cada vez mais frequente. Esses microrganismos são capazes de produzir diversos metabólitos com alto valor agregado, entre eles, os carotenoides. Por conta dos benefícios à saúde e seus pigmentos, a demanda por carotenoides naturais aumentou nos últimos anos. Os carotenoides podem ser utilizados nas indústrias de alimentos, rações, cosméticos e nutracêuticos, entretanto existem desafios associados à produção em massa dos carotenoides por microalgas, o principal é o custo não competitivo, em comparação com produtos alternativos obtidos por síntese química. Esta revisão objetivou o estudo dos carotenoides produzidos por microalgas; os principais fatores que influenciam; e a análise da viabilidade industrial desse pigmento, principalmente, no Brasil. De acordo com as estimativas, o mercado global de carotenoide deve chegar a USD 2,0 bilhões em 2026, e o Brasil, em 2019, importou USD 3,5 milhões de carotenoides. Os corantes produzidos nacionalmente são majoritariamente por via de extração vegetal, o que torna a produção por via biotecnológica um potencial a ser explorado no país. O uso de microalgas como matérias-primas para os carotenoides deve crescer, têmse realizado muitas pesquisas com intuito de otimizar essa produção e torná-la cada vez mais comerciável
Literature review: Growth of microalgae for the production of carotenoids
Keywords: Carotenoids; Microalgae; β-carotene; Astaxanthin; Carotenoides; Microalgas; β-caroteno; Astaxantina.